Adsorption Mechanisms and Structures of Arsenic Removed (Journal of Pure and Applied Sciences (Science Forum), 2025)
The toxicity of arsenic ions and salts in the environment (air, water, and land) hasmade it among the most common elements that have to be removed or reduced inthe environment. This paper proposed possible mechanisms of arsenic removal orreduction by powdered raw eggshells through adsorption techniques. Raw eggshellsfrom chickens were collected from an institutional farm in Nigeria. These collectedraw eggshells were washed with distilled water to remove impurities, air dried toreduce the moisture content and powdered using a Silver Crest blender. EnergyDispersive Spectroscopy and scanning electron microscope images of the powderedeggshell were evaluated at selected magnifications. The study revealed that themajor elemental components of the powdered eggshells are aluminium (between1.25 and 7.58 % of the adsorbent as aluminium), Calcium (between 3.7 % and 10.12% of the adsorbent as calcium), Silicon (between 11.15 % and 25.62 % of theadsorbent as silicon), Carbon (between 0.00 % and 27.75% of the adsorbent ascarbon) and oxygen (between 48.75and 58. 13% of the adsorbent as oxygen) hadthe highest weight percentages. The other elements present in the adsorbentstructure were Na, Mg, K, and Fe. It was revealed based on the components ofeggshell and previous studies that the possible mechanisms of arsenic removal bypowdered eggshell include: ( ) 2 4 3sFe OH H AsO Fe OAsO H OH− − − + → − +2 2 4 2 4XMnOOH H AsO XMnOOH H AsO+ −+ → −( )2 2 4 2 2 42XMgOH H AsO XMgOH H AsO+ −+ → −3 4 4 2SOH H AsO SHAsO H O H− ++ + +( ) ( )2 4 2 2 4( )2 ssM OH H AsO M OH H AsO− −+  −The study concluded that the removal or reduction of arsenic by powdered eggshellsis a function of the following factors pH of the aqueous solution, the composition ofthe aqueous solution, the presence of hydroxyl groups ions and the nature of theaqueous solution. The mechanism of arsenic removal includes redox, H-bond andsurface complexation formations, electrostatic attraction, oxic and anoxicreactions.